1997
DOI: 10.1128/mcb.17.6.2985
|View full text |Cite
|
Sign up to set email alerts
|

Exon Skipping and Circular RNA Formation in Transcripts of the Human Cytochrome P-450 2C18 Gene in Epidermis and of the Rat Androgen Binding Protein Gene in Testis

Abstract: The cytochrome P-450 2C18 gene was found by reverse transcription-PCR to represent the most abundantly expressed gene of the P-450 2C subfamily in human epidermis. However, in addition to the canonical mRNA of nine exons, transcripts that have skipped exon 4 or 5, exons 4, 5, and 6, or exons 4, 5, 6, and 7 were also identified in this tissue. Remarkably, circular RNA transcripts synthesized by the joining of the donor and acceptor splice sites of the same exon were detected in human epidermis for exons 4 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
140
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 26 publications
4
140
1
1
Order By: Relevance
“…Such RNAs were described for the testis-determining gene Sry in adult mouse testis (32), the human ets-1 gene (33), the human cytochrome p-450 2C18 gene in epidermis, and the rat androgen-binding protein gene in testis (31). Exons skipped during alternative pre-mRNA processing could be indeed present in a circular molecule that has the donor site of the 3Ј exon joined to the acceptor site of the 5Ј exon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such RNAs were described for the testis-determining gene Sry in adult mouse testis (32), the human ets-1 gene (33), the human cytochrome p-450 2C18 gene in epidermis, and the rat androgen-binding protein gene in testis (31). Exons skipped during alternative pre-mRNA processing could be indeed present in a circular molecule that has the donor site of the 3Ј exon joined to the acceptor site of the 5Ј exon.…”
Section: Discussionmentioning
confidence: 99%
“…Exon scrambling is an event that has often been also associated with circular RNA molecules (30,31). Such RNAs were described for the testis-determining gene Sry in adult mouse testis (32), the human ets-1 gene (33), the human cytochrome p-450 2C18 gene in epidermis, and the rat androgen-binding protein gene in testis (31).…”
Section: Discussionmentioning
confidence: 99%
“…The length of the skipped exon appears to be one key determinant, 41 but other factors such as RNA secondary structures and the speed of lariat debranching are also likely to be involved. Interestingly, a correlation between exon skipping and circular RNA biogenesis has been noted at other genes 49,50,52,55 and in a global transcriptome analysis of human endothelial cells. 90 Detailed analyses are now required to determine if re-splicing truly occurs at these loci.…”
Section: Circular Rnas Generated Via Exon Skippingmentioning
confidence: 99%
“…This was the first hint that the dominant output of a gene could, in some cases, be a circular RNA rather than a linear mRNA. 48 A handful of additional circular RNAs were identified over the ensuing years [49][50][51][52][53][54][55][56] until deep sequencing efforts combined with new computational algorithms all of a sudden revealed thousands of previously missed circular RNAs from eukaryotic cells. 13,14,27,29,31,33,40,57,58 Over 25,000 putative circular RNAs, derived from »15% of actively transcribed genes, were identified in human fibroblasts alone.…”
Section: Introductionmentioning
confidence: 99%
“…1 Additional studies reported further new examples of circRNAs over the years, [2][3][4][5][6][7][8][9] yet the extent of the prevalence of the circularization phenomenon was not clear, as the available examples remained limited. The advent of high-throughput sequencing revealed that circRNAs are a large class of abundant RNAs with complex developmental-and cellspecific expression patterns.…”
Section: Introductionmentioning
confidence: 99%